Cosmopolitanism and Hume's general point of view. (July 2014) - McArthur, Neil
Hume's writings, taken as a whole, address a dazzlingly broad range of topics. I argue that they do so as part of a coherent and interesting philosophical programme. While Hume's doctrine of the general point of view provides an attractive way of understanding the process of moral judgement, it raises the threat of parochialism – that is, it potentially makes us prey to the limitations and prejudices of our society. I show that Hume endorses what I call "engaged cosmopolitanism", which provides the resources to explain how we can, under certain circumstances, escape such parochialism. Engaged cosmopolitanism is the product of a particular sort of society – one that is open and commercial, and that governed by a system of equitable laws. Like Mandeville, Hume rejects the suspicion of commerce and "luxury" that was prevalent during his time. But he provides supporters of commercial society with a justification that does not, in contrast to Mandeville's writings, abandon notions of morality altogether. On the contrary, he makes commerce a precondition to a society's moral development. And he further links this development to a certain type of liberal political institutions, thus giving such institutions a moral basis.